Silicon changes C:N:P stoichiometry of sugarcane and its consequences for photosynthesis, biomass partitioning and plant growth - Frazao, Joaquim Jose [UNESP]; Prado, Renato de Mello [UNESP]; Souza Junior, Jonas Pereira de [UNESP]; Rossatto, Davi Rodrigo [UNESP] (Nature Publishing Group, 2020)
Silicon (Si) application has improved yield and stress tolerance in sugarcane crops. In this respect, C:N:P stoichiometry makes it possible to identify flows and interaction between elements in plants and their relationship with growth. However, few studies have investigated the influence of Si on physiological variables and C:N:P stoichiometry in sugarcane. As such, this study aimed to assess the effect of increasing Si concentrations on the growth and stoichiometric composition of sugarcane plants in the early growth stage. The experiment was conducted in pots, using four Si concentrations (0, 0.8, 1.6 and 3.2 mM). Biomass production, the concentration and accumulation of C, N, P and Si as well as the relationship between them were assessed. Silicon application increased biomass production, the rate of photosynthesis, instantaneous carboxylation efficiency and C, N, P and Si accumulation, in addition to altering stoichiometric ratios (C:N, C:P, N:P and C:Si) in different parts of the plants. The decline in C concentration associated with greater N and P absorption indicates that Si favoured physiological processes, which is reflected in biomass production. Our results demonstrate that Si supply improved carbon use efficiency, directly influencing sugarcane yield as well as C and nutrient cycling.